Exploring Kohl from a Hadith Perspective and Its Impact on Social Life - Rayyn, I Gusti Bagus Agung Perdana; Fitri Utami (Pascasarjana, Universitas Islam Negeri Alauddin Makassar, 2023)
This article focuses on Prophet Muhammad's hadith-reports about kohl, specifically those made from iṡmid, which is a Sunnah of the Prophet Muhammad. The article examines two main topics: the interpretation of the hadith regarding the use of kohl made from iṡmid and its impact on applicative, health, and economic aspects. To gain a comprehensive interpretation and understand its implications, interpretive analysis (textual, intertextual, and contextual) is necessary. This research is literature-based and relies on literature related to the research object. The conclusion of this study is that the use of kohl made from iṡmid is highly recommended, even though ṡmid is not the only material used for making kohl. Wax made from iṡmid should be used regularly before bedtime or as a cosmetic to maintain eye health. On the other hand, ṡmid should be used as a raw material for making eyeliner. This can have a positive impact on increasing economic power in the beauty or fashion sector.